Farmer Group of Cabe Bakul (Lada Katokkon) in Rantepao District, North Toraja Regency: Kelompok Tani Cabe Bakul (Cabe Katokkon) Di Kecamatan Rantepao Kabupaten Toraja Utara - A. Sry Iryani; Agustina Deka Minggu Bali (Yayasan Ahmar Cendekia Indonesia, 2021)
Chili is one of the most important foods for traditional Indonesian food. One of the chilies that have a very high Scoville rating from Toraja Utara and Tana Toraja is Cabe Bakul or Lada Katokkon. This chili is different from other peppers ranging from the shape that resembles a pabrika but the size is small, it is sweet taste turned hot and good smelled. . The disadvantage of this chili is the condition of chilies that have a very high water content so it is easy to rot and wrestle so that the price quickly goes down and sometimes thrown away. To avoid the problem, the team proposes to process chili into a product but does not change the taste, color, and smell. This activity helps the chili farmers to process their crops into processed products that have higher economic value. There are two types of products produced are Chili powder (Bon Cabe) and sauce. Chili sauce is made there are four variants of flavors are: original, onion, terasi, and fish. Through this training, the farmer group partners can cultivate the harvest and its products can compete in the Toraja market and outside Toraja. Abstrak Cabe merupakan salah satu makanan terpenting untuk makanan tradisional Indonesia. Salah satu cabai yang memiliki rating Scoville sangat tinggi dari Toraja Utara dan Tana Toraja adalah Cabe Bakul atau Cabe Katokkon. Cabe ini berbeda dengan cabe lainnya mulai dari bentuknya yang menyerupai pabrika namun ukurannya kecil, rasanya manis berubah menjadi panas dan harum. Kekurangan dari cabe ini adalah kondisi buah cabe yang memiliki kandungan air yang sangat tinggi sehingga mudah membusuk dan bergelut sehingga harganya cepat turun dan kadang dibuang begitu saja. Untuk menghindari masalah tersebut, tim mengusulkan untuk mengolah cabe menjadi sebuah produk namun tidak merubah rasa, warna dan baunya. Kegiatan ini membantu petani cabe mengolah hasil panennya menjadi produk olahan yang memiliki nilai ekonomi lebih tinggi. Ada dua jenis produk yang dihasilkan yaitu bubuk cabe (Bon Cabe) dan saos. Kuah sambal yang dibuat ada empat varian rasa yaitu: original, bawang, terasi dan ikan. Melalui pelatihan ini para mitra kelompok tani dapat membudidayakan hasil panen dan produknya dapat bersaing di pasar Toraja dan luar Toraja.